Mutu Fisik Sabun Padat Ekstrak Biji Kopi (Coffea Robusta) - Misgiati, Misgiati; Ardianto, Rahmat (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2024)
Soap is a cleaning product produced from the reaction between oil or fat with potassium hydroxide or sodium hydroxide base. Based on its consistency, soap is divided into two types, namely liquid soap and solid soap. Solid soap is more often used by the public. Utilization of natural ingredients as an innovation for soap is still rarely done. The content of coffee is able to prevent premature aging of the skin, function to smooth the skin, and neutralize irritated skin. This study aims to determine the physical quality and pH of solid soap mixed with coffee extract. Production of coffee extract using the maceration method with 70% ethanol solvent. This type of research is descriptive, with the aim of knowing the physical quality and pH of solid body soap by adding coffee extract. Based on the results of the research conducted, it can be concluded that the results of the evaluation of the physical quality of the coffee extract solid soap preparations fulfilled the physical quality test requirements, which included organoleptic tests, water content tests, foam stability tests, and pH.